2011
DOI: 10.1111/j.1740-0929.2010.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcitonin on adrenocorticotropic hormone secretion stimulated by corticotropin‐releasing hormone in the hen anterior pituitary

Abstract: The presence of a receptor for calcitonin (CT) and the effect of chicken CT (cCT) on adrenocorticotropic hormone (ACTH) secretion stimulated by rat/human corticotropin-releasing hormone (rhCRH) in the hen anterior pituitary were studied. The specific [(125)I]cCT binding component was present in the plasma membrane of hen anterior pituitary and this binding component had properties of a receptor which has binding specificity to cCT, reversibility, saturable binding, high affinity and limited capacity. When ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Therefore, the binding component for cPTHrP in plasma membrane fractions of the anterior pituitary is likely to be a receptor for cPTHrP. The order of magnitude of K d and B max values was also the same as that of luteinizing hormone-releasing hormone receptor (Kawashima et al, 1992) and calcitonin receptor (Nakayama et al, 2010b) in the hen anterior pituitary.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, the binding component for cPTHrP in plasma membrane fractions of the anterior pituitary is likely to be a receptor for cPTHrP. The order of magnitude of K d and B max values was also the same as that of luteinizing hormone-releasing hormone receptor (Kawashima et al, 1992) and calcitonin receptor (Nakayama et al, 2010b) in the hen anterior pituitary.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, it was reported that calcitonin enhances the secretion of ACTH from the anterior pituitary via its receptor (Nakayama et al, 2010b). However, it has not been reported whether PTHrP is involved in the regulation of ACTH secretion in the anterior pituitary of hens.…”
Section: Introductionmentioning
confidence: 98%
“…Chicken CT (cCT; Bachem AG, Bubendorf, Switzerland) was labeled with 125 I using Iodogen (Takahashi et al . 1993; Nakayama et al . 2010a).…”
Section: Methodsmentioning
confidence: 99%
“…2008). Recently, it was reported that CT acted directly on the anterior pituitary via its receptor binding and enhanced the amount of adrenocorticotropic hormone (ACTH) secretion stimulated by corticotropin‐releasing hormone (Nakayama et al . 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation